Seed security for smallholders - Minofu Sibale, Elizabeth Mary (Technical Centre for Agricultural and Rural Cooperation, 2001)
Seed is the most important input in agriculture and, compared to fertilisers, pesticides and labour, still the cheapest. Two keys to better yields are good cultural practices and the improvement of local, open-pollinated varieties.A major problem in...